Fault tolerant operation of kinematically redundant manipulators for locked joint failures - Maciejewski, Anthony A., author; Lewis, Christopher L., author; IEEE, publisher (Colorado State University. Libraries, 1997)
This paper studies the degree to which the kinematic redundancy of a manipulator may be utilized for failure tolerance. A redundant manipulator is considered to be fault tolerant with respect to a given task if it is guaranteed to be capable of performing the task after any one of its joints has failed and is locked in place. A method is developed for determining the necessary constraints which insure the failure tolerance of a kinematically redundant manipulator with respect to a given critical task. This method is based on estimating the bounding boxes enclosing the self-motion manifolds for a given set of critical task points. The intersection of these bounding boxes provides a set of artificial joint limits that may guarantee the reachability of the task points after a joint failure. An algorithm for dealing with the special case of 2-D self-motion surfaces is presented. These techniques are illustrated on a PUMA 560 that is used for a 3-D Cartesian positioning task.
Keywords: manipulator kinematics; kinematically redundant; fault tolerance; manipulators; redundant systems; Jacobian matrices